Pencegahan Stunting pada 1000 HPK - Yuwanti Yuwanti; Laily Himawati; Meity Mulya Susanti (LPPM Akbid Harapan Ibu Pekalongan, 2022)
Stunting is a chronic nutritional problem in toddlers with shorter height than from the age of the child. Stunting is caused by many factors such as maternal health conditions, maternal nutrition, history of disease in the mother, nutritional intake in newborns and toddlers, social and economic conditions, clean water sanitation, disease infections. The impact of stunting on toddlers can lead to increased morbidity and mortality in children, impaired child development and growth, increased health costs, decreased productivity, increased risk of disease, reproductive health problems, to non-optimal working capacity in the future. The purpose of community service is to provide health education about stunting, the causes of stunting, the impact of stunting and the impact of stunting. The method of activity is health education (Promoting) in 45 participants of kesehatan cadres and PKK members. The results of health education activities that amounted to 75.6% knowledge about stunting is good, and 24.6% knowledge about stunting is sufficient.